Effects of bee propolis supplementation on Lysozyme and lactoferrin responses following prolonged running in recreational Athletes - SITI A. A. RAHMAN,; FOONG K. OOI,; AYU S. MUHAMAD, (International Journal of Pharma and Bio Sciences, 2017)
In this study, 11 recreational athletes (age: 21.0 ± 1.5 years old) were recruited. The participants performed a running trial without bee propolis supplementation followed by another running trial after 4 weeks of bee propolis supplementation (2 tablets per day, each tablet contained 500 mg of bee propolis). Each trial consisted of warm-up by running on treadmill at 50% VO2max for 5 min followed by running at 60% VO2max for 90 min. Saliva samples (2 ml) were collected at pre-, post- and 1h post-exercise. Saliva was analysed for salivary lysozyme and lactoferrin concentrations. Results revealed that there were no statistically significant differences in saliva flow rate, lysozyme and lactoferrin concentrations and secretion rates between both running trials. As a conclusion, 4 weeks of bee propolis supplementation did not elicit positive effects on mucosal immunity following prolonged running in recreational athletes. This might be due to poor bioavailability of the bee propolis in human body and insufficient supplementation’s period and dosage.